2015
DOI: 10.1002/humu.22936
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read Single Molecule Real-Time Full Gene Sequencing of Cytochrome P450-2D6

Abstract: The CYP2D6 enzyme metabolizes ~25% of common medications, yet homologous pseudogenes and copy-number variants (CNVs) make interrogating the polymorphic CYP2D6 gene with short-read sequencing challenging. Therefore, we developed a novel long-read, full gene CYP2D6 single-molecule real-time (SMRT) sequencing method using the Pacific Biosciences platform. Long-range PCR and CYP2D6 SMRT sequencing of 10 previously genotyped controls identified expected star (*) alleles, but also enabled suballele resolution, diplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 38 publications
1
92
0
1
Order By: Relevance
“…Our designed custom genomic tool PharmArray (based on the TaqMan OpenArray) was of great help to this aim. Although tests based on next‐generation sequencing (NGS) technologies have been reported in the literature, we found that our platform results are much more suitable for the clinical approach in terms of simplicity of analysis, turnaround times, and affordable costs in our NHS. This genotyping tool allowed us the implementation of a semipreemptive strategy with eight preestablished protocols agreed upon with various clinical services in risk populations.…”
Section: Discussionmentioning
confidence: 97%
“…Our designed custom genomic tool PharmArray (based on the TaqMan OpenArray) was of great help to this aim. Although tests based on next‐generation sequencing (NGS) technologies have been reported in the literature, we found that our platform results are much more suitable for the clinical approach in terms of simplicity of analysis, turnaround times, and affordable costs in our NHS. This genotyping tool allowed us the implementation of a semipreemptive strategy with eight preestablished protocols agreed upon with various clinical services in risk populations.…”
Section: Discussionmentioning
confidence: 97%
“…The long reads allow for accurate variant calling as well as phasing of multiple heterozygous variants whose genomic location might be several kilobases apart. As such, SMRT provides an excellent technology for the sequencing of complex CYP loci and, using CYP2D6 as an example, has been demonstrated to allow the simultaneous detection of SNVs and CNVs in multiplexed samples [122,123]. In addition to genomic sequencing, SMRT allows direct decoding of epigenetic marks [124].…”
Section: Emerging Technologies Facilitating Biomarker Discoverymentioning
confidence: 99%
“…Lab 1 validated [23] the PacBio circular consensus sequencing method [24] specifically for use in confirmation. This method provides high accuracy [25] and has been successfully applied in other clinical genetic tests [26]. Lab 2 used only Sanger confirmation.…”
Section: Methodsmentioning
confidence: 99%